Analysis method for the optimal design of helicopter main gearboxes with a combination of structural and thermal influence - James, B.; Park, Y.; Grant, G. (My University, 2017)
One of the safety critical systems of a rotorcraft is the drivetrain, and within that the transmission. This system has the role of transferring power and rotational speed from the engine to the rotor blades. The transmission in a rotorcraft typically operates in a much more challenging environment than is experienced in other types of vehicle, and the performance and reliability of the transmission is critical and directly related to safety. The stringent weight requirements also impose limits on cooling system design, and the hovering flight requirement can produce quite a challenge thermally as no cooling air flow is coming from the vehicle motion. As such, helicopter transmissions tend to have to tolerate high operating temperatures. However, the analysis methods established for assessing the transmission under flight loads are typically based on experience. This experience based approach does not lend itself to assessing important trade-offs such as reliability, efficiency and weight early in the design process. Having to rely on testing for confirmation of some aspects of performance means that opportunities for optimising and improving transmission systems are lost and, even if performed, analysis optimisation studies not including the thermal effects may later turn out to not be sufficient. All of this can lead to high expense and time incurred due to issues with the design often only being identified at the testing stage. It is known that structural loads are a major consideration in the design process as it determines the size and weight of the gearbox and its sub components to ensure robustness. The industry has well established design procedures to address failure modes from structural loads, however, failure modes of coupled structural and thermal influences are not so well understood. It has been observed in recent years that thermal influences can accelerate fatigue damage leading to significant safety issues in helicopters. Romax has developed experience in these areas through collaborative research and industrial projects, giving us good insight into how to couple structural and thermal influences, and we believe that these methods can help design and development engineers in the rotorcraft industry to avoid potential failures in helicopters drivetrains.